Ochrona prawna dóbr kultury podczas trwania konfliktów zbrojnych – aspekty karnoprawne w kontekście agresji Federacji Rosyjskiej na Ukrainę - Trzciński, Maciej (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The threat to cultural goods during military operations is still a real problem, as evidenced by the barbaric aggression of Russia against Ukraine. Every war is associated with the plunder and destruction of cultural heritage, as evidenced not only by the experiences of the World War II, but also the recent wars in Iraq and Syria, where historical monuments were plundered and destroyed. Cultural heritage, especially its part which may be called national heritage, very often determines the identity of a nation, and therefore its preservation is extremely important. The experience of many wars allowed for the creation of a separate system for the protection of cultural goods in the event of armed conflicts also under international law. Poland, as a country greatly affected by the losses suffered by its national heritage during World War II, is still trying to find and recover monuments and works of art stolen by its occupiers. The protection of national heritage is the task of the state. The system of protection of cultural heritage in force in Poland is based primarily on regulations in the field of administrative law; however, ratified acts of international law and selected regulations of domestic law also provide for criminal law protection of cultural goods in the event of an armed conflict.
Keywords: dziedzictwo kulturowe; ochrona dóbr kultury; konflikty zbrojne; zniszczenia i grabieże; kulʹturna spadŝina; ohorona kulʹturnih cìnnostej; zbrojnì konflìkti; rujnuvannâ ta rozgrabuvannâ